Effect of blast furnace slag on the fresh and hardened properties of volcanic tuff-based geopolymer mortars - Abderrachid Boumaza; Mohamed Lyes Kamel Khouadjia; Haytham F. Isleem; Oualid Mahieddine Hamdi; Mohammad Khishe (Scientific Reports)
Abstract Volcanic tuffs are abundant in several regions of the world, and their use has emerged as an economically viable alternative for geopolymer production. This study investigates the effects of incorporating 0 to 30% blast furnace slag (BFS) into volcanic tuff (VT)-based geopolymer mortars cured at room temperature and 80 °C on various properties, including setting time, mechanical strength (compressive and flexural), workability, water absorption and microstructure. Infrared spectroscopy (FTIR) was used to characterize the geopolymer mortars. Sodium hydroxide and sodium silicate are used as alkaline activators. Results revealed that pure VT pastes exhibited exceptionally long setting times, approximately 48 h. However, replacing 10% of VT with Blast Furnace Slag (BFS) reduced this to 435 min. The effect of BFS on compressive strength was time-sensitive. At 7 days, a substantial increase from 2.42 MPa to 9.03 MPa was observed with 30% BFS incorporation. Conversely, under ambient curing, 28-day strength decreased. However, curing at 80 °C for 48 h improved 28-day strength to 15.03 MPa with 30% BFS. Furthermore, results revealed that incorporating 30% BFS significantly enhanced workability, resulting in a 92.08% reduction in flow time. Absorption water and Microstructural analysis confirmed a strong correlation between the degree of geopolymerization and mechanical performance. These findings highlight BFS as a promising additive for optimizing VT-based geopolymer mortars.